TRAINING CURRICULUM TO ENHANCE INSTRUCTIONAL DESIGN ABILITY ON LIFE SAFETY OF HEALTH EDUCATION TEACHERS - Somkratoke, Chayaphat; Sarayuthpitak, Jintana; Rodpipat, Sarinya (Academic Journal of Thailand National Sports University, 2022)
This research aimed to develop a training curriculum to enhance instructional design ability on life safety of health education teachers. The study was divided into 3 stages. The first stage review of the research literature on enhancing instructional design ability on life safety of health education teachers in order to synthesize the concepts used to construct the training curriculum. The second stage was to construct the training curriculum by applying the results from need survey of the health education teachers together with the applying competency based instruction with professional learning community concepts. The third stage was to examine the quality of the training curriculum which was evaluated by 5 experts. The evaluation consisted of 2 aspects which were 1) Evaluate the curriculum suitability using the curriculum suitability assessment form 2) Assess the consistency of the curriculum using a questionnaire with a scale for estimating 5 levels. The results demonstrated that the elements of the training curriculum consisted of 1. Principles and rationale of the training curriculum. 2. Objectives of the Training curriculum 3. Content structure of the training curriculum 4. Training activities 5. Media and learning resources for the training course 6.Training period 7. Assessment and Evaluation of the training curriculum and 8. Lesson plans of the training curriculum comprised of 6 units which were 1) Analysis of learners 2) Determination of behavioral learning objectives 3) Course description 4) Learning management process 5) learning materials and resources and 6) assessment and evaluation. Each unit consisted of (1) contents (2) learning objectives (3) course description (4) learning management process (5) learning materials and resources and (6) assessment and evaluation methods. The training period was 3 days. The result of the quality assessment of the developed training curriculum had a total mean of 4.28. Thus, it can be interpreted that the course was appropriate and the curriculum consistency index value of 1.